Quality Assessment and Antioxidant Activities of the Blossoms of Inula Nervosa Wall. (2nd December 2020) - Hu, Li-Xia; Luo, Mei-Feng; Guo, Wen-Jing; He, Xiao; Zhou, Jun; Qiu, Xiao-Yu; Gong, Jian-Ping; Li, Meng-Chu; Chen, Xin-Tao; Wu, Dong; Huang, Wen-Ping
Abstract: Background: Currently, although Inula nervosa Wall is substantially investigated, little is understood about blossoms of Inula nervosa Wall (BINW). Objective: In this work, we systematically investigated the antioxidant activity of the extract from BINW by various standard assays including 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical ability, 2, 2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) di-ammonium salt radical cation (ABTS), and ferric reducing antioxidant potential (FRAP). Methods: Chemical compounds were tentatively identified through an UHPLC-QTOF-MS system. Furthermore, the contents of nine compounds were detected with UHPLC method coupled with photodiode array (PDA) detector. By carefully analyzing the quantitative data via clusters analysis and principal component analysis (PCA). Results: Forty-six compounds were tentatively identified, and our results showed that nine compound samples in 21 batches of BINW collected from different areas could be differentiated and analyzed by a heatmap visualization. In addition, the contents of nine compounds (flavonoids, phenolic acids) exhibited a total of higher amounts and better antioxidant activities from Yunnan than those from the other three origins. Conclusions: Our study not only developed a powerful platform to explain the difference between traditional Chinese medicines species that are closely related through the chemometric and chemical profiling, but also presented a useful method to establish quality criteria of BINW with multiple origins. Highlights: To characterize the BINW in detail, we not only performed DPPH, FRAP, and ABTS assays to investigate its antioxidant activity, but also established UHPLC-QTOF-MS/MS- and UHPLC-PDA-based methods to comprehensively identify and qualitatively analyze its components.